2012
DOI: 10.1080/17482798.2011.630742
|View full text |Cite
|
Sign up to set email alerts
|

Pre-pubescent girls' evaluations of female images in Hong Kong media

Abstract: Interviews with pre-pubescent girls in Hong Kong explored their satisfaction with the images of females presented in the media. Sixteen girls aged 10 to 12 were asked to take images from media that are about "what girls or women should be or should not be; and what girls or women should do or should not do". They were asked who created the images they collected and whether they were satisfied with the content.Most of these young girls were able to identify some of the individuals and the institutions involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…Some participants used beauty and slimming ads to illustrate what they perceived as inappropriate or undesirable gender roles. The critical reading and dissatisfaction with female images that are too thin or too near perfection are similar to the findings previously reported among pre-adolescents girls in Hong Kong (Chan, 2011a). Similar to what was reported in Chan's 2011 study, the adolescent girls in this study showed approval of female images in advertisements that they considered natural looking and as wearing clothes that were not too sexy, even though the approved images displayed light make-up.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Some participants used beauty and slimming ads to illustrate what they perceived as inappropriate or undesirable gender roles. The critical reading and dissatisfaction with female images that are too thin or too near perfection are similar to the findings previously reported among pre-adolescents girls in Hong Kong (Chan, 2011a). Similar to what was reported in Chan's 2011 study, the adolescent girls in this study showed approval of female images in advertisements that they considered natural looking and as wearing clothes that were not too sexy, even though the approved images displayed light make-up.…”
Section: Discussionsupporting
confidence: 88%
“…Qualitative studies have examined what types of media images attract the attention of pre‐adolescent girls in Hong Kong and how they perceived the images presented (Chan, 2011a; Chan, 2011b; Chan et al , 2011). Pre‐adolescent girls' perceived gender roles were shown to combine traditional and contemporary female role stereotypes.…”
Section: Learning Gender Roles From Advertising Imagesmentioning
confidence: 99%
See 1 more Smart Citation
“…The socialization of children into active, participating consumers is inevitable and necessary given the economic system (Preston, 2004; 364) yet there is still great debate around the impact of advertising and marketing to children (Nairn and Fine, 2008). Research continues to increase in many areas related to children and consumption, including research around the pursuit of beauty (Scelzo and Lerman, 2009;Northup and Liebler, 2010;Chan, 2012;McGladrey, 2014), with the impact that media has on this pursuit becoming an important research area (Jung and Peterson, 2007). Authors such as Tiggemann, Slater and Sharpe have been instrumental in researching the impact that media has on body image perceptions of women (Tiggemann, 2004;Sharp, Tiggemann and Mattiske, 2015) and adolescent girls (Slater et al, 2012;Tiggemann and Slater, 2013).…”
Section: Children and Consumptionmentioning
confidence: 99%